Makna Teologis Konsep “Oikumene” Menurut Yohanes 17:1-26 dan Aplikasinya Bagi Gereja Masa Kini - Dina Kristiani; Paulus Kunto Baskoro (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
AbstractThe church has an important role in a movement for the gospel of Jesus Christ. The Great Commission is the center of the church in carrying out the mission of the Kingdom of God in this wolrd. Since the days of the early church, the church has experienced tremendous growth. Many souls believed in Jesus and experienced tremendous spiritual growth. The extraordinary growth of God’s church makes all components of the church must be well integrated into a unified whole. All of this cannot be separated from the Lord Jesus prayer so that His disciples remain united in the project of the great commission. But in reality, the church that should have remained united as the Lord Jesus prayer in John 17:1-26 did not materialize well. The church began to fokus on worldly interests and was no longer a universal church unit. Some of the problem that occurred, the disorganization of the church which is often referred to as ecumenical did not happen well, because of differences in doctrine, there are elements of self-interest, leadership problem and finanacial problems. So that the essence of the church to carry out the mission of the great commsission has shifted. This writing uses a descriptive method of literature by extracting library data ro strengthen understanding as a whole. The goal is that through writing, namely, First, church leaders realize how important a unity is in God’s church. Second, the church becomes a pleasant family as a member of the body of Christ. Third, believers are focused again on thinking about the realization of the Lord Jesus prayer, so that they become one.. Keywords:  Ecumenical, Unity, Church, Christian, Jesus Prayer.